2006
DOI: 10.1182/blood-2006-10-052787
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin provides an accessory signal to enhance T-cell activation by signaling through the 5-HT7 receptor

Abstract: IntroductionThe central and peripheral nervous systems can modulate immune function by releasing soluble factors such as hormones, neuropeptides, and neurotransmitters. 1,2 Serotonin (5-HT) is a classical neurotransmitter and vasoactive amine best known for its role in the regulation of variety of physiologic states and behaviors, including pain, appetite, mood, and sleep. 3 Despite these major roles for 5-HT in the central nervous system, the vast majority of 5-HT is produced in the periphery (Ͼ 90%), primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
274
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(290 citation statements)
references
References 46 publications
(73 reference statements)
6
274
2
8
Order By: Relevance
“…Traditionally, it has been thought that the functions of immune cells such as T cells and DCs are regulated mainly by cytokines. However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 73%
“…Traditionally, it has been thought that the functions of immune cells such as T cells and DCs are regulated mainly by cytokines. However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 73%
“…The 5-HT 2A is linked to cell signaling through the JAK-2/STAT pathway (21), and there are studies suggesting that 5-HT 2A is present on activated T lymphocytes (4,5). One possible explanation, therefore, is that these joint ADRs could be of inflammatory origin.…”
Section: Discussionmentioning
confidence: 99%
“…Seven main groups of serotonin receptors with their corresponding subgroups have been identified (3). Serotonin receptor subtype 2A (5-HT 2A ) is located on neurons, but also on platelets, vascular smooth muscle (3), and probably also on immune cells (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…These results further strengthen the notion that the 5-HT 7 receptor plays an important role in immune activation and colitis pathogenesis. It is important to note, however, that the 5-HT 7 receptor has also been shown to be expressed on T cells where they play an important role in early T cell activation events (71). Thus, treatment with SB-269970, for example, may also have an effect on T cells.…”
Section: Cd11cmentioning
confidence: 99%